An Analysis of the Migration of Turks of Bulgaria to Turkey in 1950-51 with the Turkey’s Domestic and Foreign Policy of the Era - Karapınar, Ahmet Can (Journal of Applied And Theoretical Social Sciences, 2021)
Movement of populations has been one of the main drivers of the history of humanity. For a geography which is at the crossroads of different cultures and civilizations such as Anatolia, this is much more relevant. Among the mass movement of migrations in Turkish history; migrations from Bulgaria, with their number of migrants and the time span, have a special place. Specifically; 1950-51 Migration, by giving us a chance to study political history of the early years of the Cold War at that geography, offers us a quite interesting study area. In this article, migration of Turks of Bulgaria to Turkey in 1950-51 would be analyzed with a special attention to the Turkey’s domestic and foreign policy of the era. In order to have a holistic understanding, first the background would be explained by studying on the situations of the respective countries during and in the aftermath of World War II. While looking to the aftermath of World War II, the process which led to the 1950-51 Migration would be studied in detail. Later, 1950-51 Migration would be studied with its implications on Turkish domestic and foreign policy. Connected to that, foreign aid issue too would be studied. Finally the conclusion would be made. The analysis shows that, 1950-51 Migration was a milestone event in the history of the Republic of Turkey which shaped Turkish domestic and foreign policy in the early years of the Cold War.